Analisis Penerapan Metode ‘Allimna untuk Mempercepat Baca Al-Qur’an - Havid, Abdul; Shohib, Moch. (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2021)
Studying and understanding the Qur'an and teaching it is a very high value worship. Learning the Qur'an is the best of Muslims and teaching the Qur'an to others is also the best of Muslims, both of these things are equally good but it will be better and more important if someone combines the two. The focus of the problem in this study 1) What is the 'Allimna method to speed up reading the Qur'an? 2) How is the application of the 'Allimna method to speed up reading the Qur'an? 3) What are the inhibiting and supporting factors of the 'Allimna method to speed up reading the Qur'an?. This study uses a qualitative-descriptive method, using a case study approach. Data collection techniques are interviews, observations, and documentation. The results of the study show that the 'Allimna method is the 'Allimna method not only offering a fast method, it turns out that the choices of the 'Allimna verse are many of the arguments for the akidah and amaliyah of Ahlussunnah Wal Jama'ah. The purpose of using the 'allimna method is to achieve better results and the first steps are in recognizing the Hijaiah letters and their makhroj, the second is the introduction of harokah, the third is the introduction of serial letters and the fourth is the introduction of the science of tajweed. The inhibiting factor for the 'Allimna method is that there are students who are lazy to repeat or re-learn lessons at home, along with tutoring activities. Supporting factors for students, students are diligent in every learning process at TPQ Al-Barokah.